Tax Literacy and Leadership Agility: Indigenous Peoples Awareness in Paying Taxes - Jamaluddin Ahmad; Hardianti Hardianti; Firmansya Firmansya; Hariyanti Hamid; Erfina Erfina (Iapa Proceedings Conference, 2020)
This study aims to identify and explain tax literacy and leadership agility at the awareness of indigenous peoples in paying taxes. Based on the report, land and building taxes' income is still low for the indigenous peoples of "towani tolotang" South Sulawesi. The research method used is descriptive qualitative with the Nvivo-12 plus program's help by taking a sample of 55 respondents of the traditional leader "uwwa" who spread to the community. Data collection techniques through in-depth interviews and documentation. The results showed that the level of tax literacy has a significant effect on the level of awareness of paying taxes. Its influence is strengthened by applying leadership agility in the form of sensitivity, leadership unity, and resource fluidity. The implication is that with a high level of tax literacy involving leadership agility, the level of awareness of paying taxes will also be higher. The importance of this research is to increase public awareness of paying taxes, although the limitations of this research are on indigenous peoples.